Interdependence Between the Belgrade Stock Exchange Development and Serbia’s Economic Growth - Stojkovic, Dragan Gradimir; Lojanica, Nemanja Milovan; Štimac, Milko Đuro (Industrija, 2019)
The goal of this research is to conduct an empirical test to determine the interdependence between the Belgrade Stock Exchange development and Serbia’s economic growth. The authors of this paper used the quarterly data about the market capitalization and turnover of shares achieved at the Belgrade Stock Exchange, as well as the quarterly data about Serbia’s gross domestic product between 2003 and 2018. During the testing of the long-term variable interconnection the Johansen (1991) co-integration test was used, whereas the Granger causality test was used for the causality analysis. The test results to date primarily show that the development of a capital market is of significance for economic growth, which implies that a liquid stock exchange may serve as a reliable indicator of a long-term growth of economic activity.
Keywords: Granger Causality Test; Economic Growth; Market Capitalization; Turnover of Shares; Belgrade Stock Exchange